A randomized phase I comparative pharmacokinetic study comparing SB5 with reference adalimumab in healthy volunteers. (3rd July 2017) - Shin, D.; Lee, Y.; Kim, H.; Körnicke, T.; Fuhr, R.
Summary: What is known and objective: SB5 is a biosimilar to the reference adalimumab (ADL) currently in development. The primary study objective was to demonstrate pharmacokinetic (PK) equivalence of SB5 to European Union‐sourced adalimumab (EU‐ADL), and United States‐sourced adalimumab (US‐ADL) in healthy subjects. Safety, tolerability and immunogenicity were also assessed as secondary objectives. Methods: In this phase I, single‐blind trial, 189 healthy volunteers were randomized to a single 40 mg dose of SB5, EU‐ADL or US‐ADL and PK was evaluated for 71 days afterwards. Serum adalimumab concentrations were measured using an enzyme‐linked immunosorbent assay (ELISA) test. PK parameters were calculated based on actual sampling times relative to dosing and non‐compartmental analysis methods, and equivalence was determined using predefined margins of 0.8‐1.25. Results and discussion: Baseline characteristics and demographics were comparable between the three groups. Mean values of area under the concentration‐time curve from time zero to infinity (AUCinf ), maximum serum concentration ( C max ) and AUC from time zero to the last quantifiable concentration (AUClast ) were similar between groups, and 90% confidence interval for these parameters were within the predefined equivalence margins for all pairwise comparisons. No discontinuations due to treatment‐emergent adverse events (TEAEs) or deaths were reported. Number and kind of TEAEs were comparable between the three groups and considered mild to moderate. The incidence of subjects with antidrug antibodies (ADA) and the overall incidence of neutralizing antibody (NAb) were comparable across the three groups. What is new and conclusion: The PK of SB5 was equivalent to that of EU‐ADL and US‐ADL. SB5 was well tolerated with similar safety and immunogenicity profile to EU‐ADL and US‐ADL.